Ekstrak Kunyit (Curcuma longa) sebagai Tatalaksana Sindrom Polikistik Ovarium - Aulia Rika Fahrumnisa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Polycystic ovary syndrome (PCOS) is a disease that often occurs in women and is a heterogeneous endocrine disease. PCOS often causes infertility in women. The major criteria for this syndrome are hyperandrogenism, hyperinsulinemia, chronic anovulation and polycystic ovaries. The causes of PCOS are multifactorial include insulin resistance, hyperlipidemia, obesity, genetics and the environment. Turmeric or Curcuma longa is a well-known plant in the treatment of inflammation of the liver. In its development it turns out that turmeric is not only useful in the treatment of liver disease, but also on PCOS. Turmeric contains curcuminoid which has anti-cancer effects because it is rich in antioxidants, anti-inflammatory, hypoglycemic, antibacterial and anti-hyperlipidemia agents. Turmeric is very well absorbed in the digestive tract, so it is very good to use orally. Therefore turmeric is best used to reduce the symptoms of PCOS.